Pengembangan Media Berbasis PhET Simulation pada Materi Pecahan Senilai di Sekolah Dasar - Ardini, Ardini; Andini, Gita (Indonesian Journal of Science, Technology, Engineering, Art, and Mathematics Education, 2024)
This study aims to develop instructional learning based on PhET simulation to improve students' understanding of equivalent fractions in mathematics. This study uses the research and development method with the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). The subjects of the PhET simulation-based instructional learning design trial were 6 fourth grade elementary school students. The results of the study showed that the use of PhET simulation-based media can increase students' interest in learning, clarify the concept of fractions, and motivate them to be more active in learning. The simulation provided is able to provide concrete visualization so that students can more easily understand the relationship between fractional parts.